Responses to 7 October, universities
1 online resource.
Keywords: "One of three volumes responding to the 7 October attack, Universities, focuses on the heartland of contemporary antisemitic thinking, which is scholarship; and its reflection in student discourse on campus. Contributions go back to Sartre and to debates of Marx's time; another looks at the New Left forged in the civil rights movement, and shows how antisemitic responses to the 2023 violence were anticipated by some of the responses to the 1967 Arab League aggression. The feminist movement and 'progressives' more generally come under scrutiny, and there is analysis of antisemitism on campus after 7 October, showing how it is tolerated and protected there; including in archeological attempts to deny that there is an ancient Jewish history in Israel. This work will appeal to scholars, students and activists with an interest in antisemitism, Jewish studies and the politics of Israel"--